Social Outcomes of School Leavers With Cerebral Palsy Living in Victoria - Imms, Christine; Reddihough, Dinah; Shepherd, Daisy A.; Kavanagh, Anne (Frontiers in Neurology, 2021)
Objective: In Australia, the National Disability Strategy provides a framework to guide actions and investment to achieve equity in social inclusion and economic participation for people with disability. We investigated the social outcomes of school leavers with cerebral palsy (CP) in Victoria, Australia and explored the determinants of desirable outcomes. Methods: We used the Victorian CP Register to invite all adults with CP aged 18 – 25 years (n=649). On-line and/or paper-based surveys explored participation in education, employment, community activities, living situation, relationships and life satisfaction. Functional and health status data were collected. Social outcomes were summarised descriptively and compared between individuals with CP and non-disabled peers aged 18 – 25 years from the Household Income and Labour Dynamics in Australia dataset. Within the CP cohort we explored whether physical and mental health and level of functioning were associated with social outcomes. Results: Ninety participants (57% male; mean age 22.4 years (SD: 2.2) in 2020; 61.1% self-reported) provided data for analyses. CP characteristics were similar between respondents and non-respondents. In comparison to similar aged peers, 79.8% had completed secondary school (compared to 83.2%); 32.6% (compared to 75.8%) were in paid work; 87.5% (compared to 48.2%) were living in their parental home; and 3.4% (compared to 31.6%) were married or partnered. Individuals with CP and higher levels of functional capacity and better physical health were more likely to undertake post-secondary education. Higher levels of functional capacity and physical health, and lower mental health status was associated with being employed. Conclusions: While foundational education completion rates were similar to non-disabled peers, significant gaps in social outcomes remain, including residence in the parental home and single status. While addressing these issues is challenging, substantial efforts are needed to reduce these disparities – work that needs to be done in collaboration with people with CP and their families.